2020
DOI: 10.1177/2309499020936009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, incidence, and survival of synovial sarcoma subtypes: SEER database analysis

Abstract: Background: Synovial sarcoma (SyS) is a rare malignancy that is typically located on the limbs and occurs predominantly in adolescents. A study in a large population for SyS comparing subtypes has not yet been reported. Methods: National Cancer Institute’s Surveillance, Epidemiology, and End Results database was queried for patients diagnosed with SyS between January 1975 and December 2016. Patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 21 publications
2
99
1
Order By: Relevance
“…We showed that the best tumor size cut-point of synovial sarcoma patients was 9.5 cm. Aytekin et al showed that male and being colored individual of synovial sarcoma patients had poorer prognosis (23). We also noticed that sex had a signi cant in uence on synovial sarcoma patient survival rate and race was correlated with overall survival.…”
Section: Discussionsupporting
confidence: 59%
“…We showed that the best tumor size cut-point of synovial sarcoma patients was 9.5 cm. Aytekin et al showed that male and being colored individual of synovial sarcoma patients had poorer prognosis (23). We also noticed that sex had a signi cant in uence on synovial sarcoma patient survival rate and race was correlated with overall survival.…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, the immediate vicinity of popliteal tumors to neurovascular structures passing through this region often limit the extent of the resection or require extensive reconstructions (8). In SyS tumor size, tumor depth, tumor localization and the ability to achieve a complete resection are all factors affecting prognosis (1,11). Risk factors for sarcoma include hereditary disorders such as: retinoblastoma, neurofibromatosis, tuberous sclerosis, familial adenomatous polyposis, Li-Fraumen syndrome, Werner syndrome and basal cell nevus syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis can reveal different patterns of chromosomal aberrations within the lesion (14,15). A commonly believed etiological cause for SyS is a chromosome abnormality known as T (x; 18) (P11.2; q11.2), that results in the formation of SS18-SSX fusion oncogenes (1,16). The chromosomal translocation leading to the production of the SS18-SSX oncogene is first defined, and represents the archetype of sarcoma associated with translocation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations